Obtención de fibra textil a partir del reciclado del plástico (PET) (2023)
The following work describes the transformation process of PET to obtain textile fiber, with the purpose of raising awareness about the importance of recycling single-use plastics to reduce their environmental impact, taking into account that this material is discarded. indiscriminately in the different components of our ecosystem, generating greater contamination due to its long decomposition time.